A germline mutation in the POT1 gene is a candidate for familial non-medullary thyroid cancer - Srivastava, Aayushi; Miao, Beiping; Skopelitou, Diamanto; Kumar, Varun; Kumar, Abhishek; Paramasivam, Nagarajan; Bonora, Elena; Hemminki, Kari; Försti, Asta; Bandapalli, Obul Reddy (Cancers, 2020)
Non-medullary thyroid cancer (NMTC) is a common endocrine malignancy with a genetic basis that has yet to be unequivocally established. In a recent whole-genome sequencing study of five families with occurrence of NMTCs, we shortlisted promising variants with the help of bioinformatics tools. Here, we report in silico analyses and in vitro experiments on a novel germline variant (p.V29L) in the highly conserved oligonucleotide/oligosaccharide binding domain of the Protection of Telomeres 1 (POT1) gene in one of the families. The results showed a reduction in telomere-bound POT1 levels in the mutant protein as compared to its wild-type counterpart. HEK293T cells carrying POT1 p.V29L showed increased telomere length in comparison to wild-type cells, suggesting that the mutation causes telomere dysfunction and may play a role in predisposition to NMTC in this family. While one germline mutation in POT1 has already been reported in a melanoma-prone family with prevalence of thyroid cancers, we report the first of such mutations in a family affected solely by NMTCs, thus expanding current knowledge on shelterin complex-associated cancers.
Gesehen am 17.09.2020